Nonprofit Revenue Generation - Micayla Richardson; Marlen Barajas Espinosa; Jennifer Jones; Kimberly Wiley (EDIS, 2022)
This publication was designed to help nonprofit organizations develop a strategic revenue generation plan that aligns with their mission and organizational capacity. The publication discusses steps in choosing a revenue strategy, as well as common mistakes to avoid. Written by Micayla Richardson, Marlen Barajas Espinosa, Jennifer Jones, and Kimberly Wiley, and published by the UF/IFAS Department of Family, Youth and Community Sciences, May 2022.